Review: trends in nanotherapeutics to manage Helicobacter pylori - R. Chitas; P. Parreira; M.C. Martins (Microbiota in Health and Disease)
Antibiotics have been extensively used in the eradication of Helicobacter pylori, but their effectiveness is hindered by the bacterium’s ability to acquire resistance. Further, the drug’s short residence time and low bioavailability in the gastric environment (low pH, presence of digestive enzymes, and difficulty in crossing the mucus layer) also challenge the treatment. Nanotherapeutics to protect and increase antimicrobials residence time in gastric settings and new bactericidal strategies based on localized formation of reactive oxygen species (ROS), after intrinsic (acidic pH) or extrinsic (light source or ultrasound device) stimulus have been developed for gastric infection management. Here the most promising nanotherapeutics published from June 2023 to June 2024, retrieved on PubMed and Scopus using the search keywords “Nanotherapeutics”, “Nanoparticles”, “Bioengineered”, “Biomaterials”, plus “Helicobacter pylori”, are briefly highlighted.